1989
DOI: 10.1007/bf00292324
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the costs and benefits of the cyanogenic system in Trifolium repens L.

Abstract: The effect of the cyanogenic glucosides linamarin and lotaustralin and their hydrolyzing enzyme linamarase was studied in a B2 generation segregating for the genes Ac and Li. Plants containing the glucosides are protected against grazing by snails both in the seedling stage and as adult plants. In seedlings, however, there is a direct effect on survival, whereas in adult plants the leaf area of plants containing linamarin/lotaustralin is less reduced under intense grazing. Linamarase has no effect on grazing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 26 publications
3
72
1
1
Order By: Relevance
“…In theory a trade-off is expected between growth/seed production and defence, as was indeed found in some studies (Coley, 1986;Kakes, 1989;Baldwin et al, 1990). In many other cases, however, no such trade-off was found (Brown, 1988;Simms & Rausher, 1987;Briggs & Schultz, 1990).…”
Section: Introductionmentioning
confidence: 73%
“…In theory a trade-off is expected between growth/seed production and defence, as was indeed found in some studies (Coley, 1986;Kakes, 1989;Baldwin et al, 1990). In many other cases, however, no such trade-off was found (Brown, 1988;Simms & Rausher, 1987;Briggs & Schultz, 1990).…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, cyanogenesis seems to be beneficial for plants under specific environmental conditions (Kakes, 1989). The distribution of cyanogenesis in populations of Lotus corniculatus L. and Trifolium repens L. depends on abiotic factors that are also determining the occurrence and activity of snails, the important herbivores of clover (Jones, 1966(Jones, , 1972(Jones, , 1988.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, cyanogenesis has been found to be an effective deterrent against generalist clover herbivores, including slugs and snails (for example, see Angseesing, 1974;Dirzo and Harper, 1982a, b;Kakes, 1989), insects (Dritschilo et al, 1979;Pederson and Brink, 1998) and small mammals (Saucy et al, 1999;Viette et al, 2000). These findings suggest that cyanogenesis is adaptive in the presence of herbivores.…”
Section: Agents and Targets Of Selection In Clover Cyanogenesis Clinesmentioning
confidence: 99%
“…These findings suggest that cyanogenesis is adaptive in the presence of herbivores. At the same time, cyanogenesis appears to be energetically costly and disadvantageous in environments with low herbivore pressure; acyanogenic cyanotypes tend to show greater flower production than cyanogenic plants in the absence of herbivores, suggesting a selective advantage for acyanogenic plants under these conditions (Kakes, 1989). These two agents of selection-herbivore pressure and energetic costs of cyanogenesis-could together account for the observed clinal variation if cooler climates are characterized by lower herbivore abundance or shorter periods of herbivory, a pattern that has been observed in other temperate ecosystems (for example, see Pennings and Silliman, 2005).…”
Section: Agents and Targets Of Selection In Clover Cyanogenesis Clinesmentioning
confidence: 99%
See 1 more Smart Citation